Analisis Efisiensi Teknik Sektor Kesehatan di Propinsi Daerah Istimewa Yogyakarta - Barokatuminalloh Barokatuminalloh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
The reseach aim is how to know the technical efficiency of health sector in every region at DIY Province. This analysis is provided in two steps. The first one is technical efficiency of health sector in every region at 2002–2006 using DEA, VRS, and CRS assumption. The second one is regressing DEA output technical efficiency scores, VRS assumptions, and input orientation using fixed effect pooling analysis method. There are two variables data of DEA, input variables and output variables. Input variables include ratio of doctors, ratio of nurses and midwifes, and bed patients, per thousand habitants, while output variables are infant survival rate, maternal survival rate, and life expectancy at birth. While the used of regression data is technical efficiency scores, that takes from DEA, use VRS assumptions and input orientations. The independent variables are education level (approximity high school and university graduated percentage), GDP per capita, and goverment health budget per capita.The first result of the research showing in general the level of health efficiency sector in every region in DIY is high enough, whereis in year 2006 the level of efficiency for four regions are 100 percent, except for Yogyakarta has decrease efficiency 33,74 percent. This is showing that Yogyakarta could be increasing their output, in this case is health level should be higher than before using the same inputs. Yogyakarta with 33,74 percent of technical efficiency level, still has lot space for improving the level of health with using the same input alocation.The second analysis showing that, GDP per capita and government budget for health sector per capita significantly influence the technical efficiency scores at every region. Whereis GDP per capita has positif influence, while the government budget for health sector per capita has negative influence. The variable of education level in this reseach doesn’t have influence the efficiency sector level of health significantly. Keywords: technical efficiency, DEA, health sector